How has social media impacted the life of an individual who publicly challenges authoritative discourse? - Radzuwan, Ab Rashid; Kamariah, Yunus; Hashmi, U.M.; Omar Din, M.A. (2020)
This paper discusses the role of social media in shaping the life of an individual who publicly challenges Islamic authoritative discourse (i.e the hadith of Prophet Muhammad and the Quran). Sally (pseudonym), a year old Malaysian lady, was the sole participant of this study where the impacts of social media on her life were investigated in-depth. Data were generated using an ethnographic approach involving a prolonged observation of her social media accounts (i.e Facebook, Blog and Twitter) for four years from to . This time period covers the major developments in her life since her public rejection of Islamic authoritative discourse to her settlement in the USA. A thematic analysis was carried out to make sense of the data. The findings reveal that social media has affected her life in both negative and positive ways. She faced several problematic experiences (e.g. break up with family, life threats, police reports and exile) due to her postings which challenge Islamic authoritative discourses, however she also made full use of the social media to finally put a stop to the problematic experiences.